The Emergence of Urban Border Spaces in Europe. Issue 4 (8th August 2019) - Fauser, Margit
ABSTRACT: Over the past few decades, nation state borders throughout the world have been undergoing major transformations. These changes are perhaps particularly salient in the supranational space of the European Union, where new, diverse governance arrangements have emerged for the control of borders and migrations. This governance now involves national and supranational, state and non-state actors and territories beyond the external borders of the European states. At the same time, transformations are affecting the city and urban spaces where a plethora of new mechanisms of control are emerging. Cities are considered key sites for the inclusion of migrants, affording them substantial (urban) citizenship. Nevertheless, little attention is being paid to the role of cities in the exclusion and control of migrants. Through devolution from above, as well as through urban autonomy, both public and non-state actors in cities are increasingly engaged in matters such as migrants' legal status, removal, and deportation. Thus, an account of the city in such control has to take issue with the notion that the urban scale is simply nested in, subordinate to, and bounded within the national state space. Rather, scales are constructed and produced, which includes the historically changing relationship of urban and national scales. Drawing on migration, border, and urban studies, this paper develops a theoretical approach that locates the city within contemporary border transformations, identifies several mechanisms of urban border control, and provides some empirical examples to illustrate these points. Against this backdrop, the paper suggests considering urban space as border space.